Supernumerary small ring chromosome. - Kaffe, S (1977)
A supernumerary small ring chromosome was found in 30% of cultured peripheral leucocytes and 50% of skin fibroblasts in a 6-year-old boy with mild mental retardation and midline cleft palate. The extra chromosome appeared to carry a densely staining region on Giemsa banding. The banding patterns of the remaining 46 chromosomes were normal. C banding indicated that the ring chromosome contained mainly centromeric constitutive heterochromatin. Chromosome analysis of both parents showed normal karyotypes by both conventional and banding techniques; thus the origin of the ring chromosome could not be determined.